2017
DOI: 10.1038/s41467-017-02002-4
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic PIK3CA induces centrosome amplification and tolerance to genome doubling

Abstract: Mutations in PIK3CA are very frequent in cancer and lead to sustained PI3K pathway activation. The impact of acute expression of mutant PIK3CA during early stages of malignancy is unknown. Using a mouse model to activate the Pik3ca H1047R hotspot mutation in the heterozygous state from its endogenous locus, we here report that mutant Pik3ca induces centrosome amplification in cultured cells (through a pathway involving AKT, ROCK and CDK2/Cyclin E-nucleophosmin) and in mouse tissues, and increased in vitro cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
57
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 58 publications
9
57
3
Order By: Relevance
“…High-depth transcriptomics confirmed that heterozygosity for PIK3CA H1047R fails to induce widespread substantial transcriptional remodeling, whether chronically modelled in CRISPR-edited iPSCs or acutely induced in mouse embryonic fibroblasts (MEFs) by Cre expression, despite induction of canonical PI3K pathway activation in both cases (current study and Ref. ( 5, 28, 48 )). Similarly, iPSCs with heterozygous expression of PIK3CA E418K , a “non-hotspot” mutation, were transcriptionally indistinguishable from their isogenic wild-type controls.…”
Section: Discussionsupporting
confidence: 56%
“…High-depth transcriptomics confirmed that heterozygosity for PIK3CA H1047R fails to induce widespread substantial transcriptional remodeling, whether chronically modelled in CRISPR-edited iPSCs or acutely induced in mouse embryonic fibroblasts (MEFs) by Cre expression, despite induction of canonical PI3K pathway activation in both cases (current study and Ref. ( 5, 28, 48 )). Similarly, iPSCs with heterozygous expression of PIK3CA E418K , a “non-hotspot” mutation, were transcriptionally indistinguishable from their isogenic wild-type controls.…”
Section: Discussionsupporting
confidence: 56%
“…At present, it is not clear whether the observed defects in cell cycle progression are an artefact of forced overexpression of supra-physiologically active PI3K constructs, or whether this would also occur upon endogenous oncogenic PIK3CA activation. In this regard, we did not find evidence for cell cycle blockade in MEFs expressing an endogenous heterozygous PIK3CA H1047R allele [72]. Oncogenic activation of PI3K signaling has also been shown to elicit senescence in some cellular contexts [91,95,96] but not in others [72,97].…”
Section: Cell Cycle Block By Constitutive Pi3k (Over)activation?contrasting
confidence: 69%
“…Our demonstration that physiological induction of PIK3CA H1047R (i.e. in the heterozygous state and expressed from the endogenous promotor) can induce centrosome amplification and aneuploidy [72] more firmly establishes this biological role of mutant PI3K. In fact, PI3K also controls tetraploidization under physiological conditions: in rodents, modulation of insulin concentration, and consequently Akt/PKB activity, orients hepatocytes into a specific cell cycle program, leading to the generation of binucleated tetraploid cells [80].…”
Section: Pik3ca/aktmentioning
confidence: 63%
See 2 more Smart Citations